Experimental Demonstration of Coherent Combining With Tip/Tilt Control Based on Adaptive Space-to-Fiber Laser Beam Coupling - Feng Li; Chao Geng; Guan Huang; Yan Yang; Xinyang Li; Qi Qiu (IEEE Photonics Journal, 2017)
A novel approach of tip/tilt control through optimizing laser beam coupling efficiencies from space to polarization-maintaining-fibers with stochastic parallel gradient descent (SPGD) algorithm for coherent beam combining (CBC) applications is proposed and demonstrated experimentally using a seven-element adaptive fiber-optics collimator (AFOC) array for the first time to the best of our knowledge. Compared with the normal target-in-the-loop SPGD method with just a single cost function, the tip/tilt control here is independent of the phase-locking control and parallel for each cell of the AFOC array. Such characteristic gives the AFOC array capacities of real-time correction of fast-changing turbulence induced tip/tilt-type phase errors. Piezoelectric-ceramic-ring fiber-optic phase compensator and AFOC are developed to correct the piston- and tip/tilt-type aberrations, respectively. The power-in-the-bucket (PIB) metric is used for phase-locking. Parallel tip/tilt control is implemented via maximizing the received power in each subaperture with fixed two-channel SPGD control. The average of normalized coupling efficiencies of seven AFOCs increases from 0.76 without tip/tilt control to 0.94 under control. In CBC, the PIB metric increases by 4.6 times, and the phase residual error is less than λ/15.